Tabu Search Method for Solving the Traveling salesman Problem - Isra Alkallak; Ruqaya Sha’ban (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research presents the fundamental concepts of tabu search for   optimization problem as symmetric traveling salesman problem. The purpose of this research is to solve the traveling salesman problem with tabu search method, to find an optimal solution of small search space and computational requirements.